2013
DOI: 10.1136/bcr-2013-009794
|View full text |Cite
|
Sign up to set email alerts
|

Cervical nodular fasciitis in a 17-month-old child

Abstract: SUMMARYNodular fasciitis (NF) is an uncommon fibroblastic proliferation that usually arises in the extremities or trunk, less frequently in the head and neck region. It is frequently mistaken for a malignant tumour owing to its rapid growth, but it is ultimately a benign condition with spontaneous regression. We describe a case of a 17-month-old African girl with cervical NF in which spontaneous and complete regression of the lesion occurred following the diagnosis by fine needle aspiration cytology. We emphas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…21 When the lesion is rapidly growing and accompanied by fever and upper respiratory tract symptoms, these lesions may be mistaken for reactive or infectious adenitis on imaging. 22 Given the rarity of nodular fasciitis and the nonspecific imaging findings, the diagnosis is rarely entertained before surgery. Regardless of this, we recommend preoperative imaging (either MRI or CT) to characterize the lesion, assess the extent of the mass, detect associated bone remodeling or destruction, and to exclude other pathologic entities that may require different management.…”
Section: Figure 1 Clinical Presentationmentioning
confidence: 99%
“…21 When the lesion is rapidly growing and accompanied by fever and upper respiratory tract symptoms, these lesions may be mistaken for reactive or infectious adenitis on imaging. 22 Given the rarity of nodular fasciitis and the nonspecific imaging findings, the diagnosis is rarely entertained before surgery. Regardless of this, we recommend preoperative imaging (either MRI or CT) to characterize the lesion, assess the extent of the mass, detect associated bone remodeling or destruction, and to exclude other pathologic entities that may require different management.…”
Section: Figure 1 Clinical Presentationmentioning
confidence: 99%
“…The gold standard therapy is surgical resection as documented by the literature 1,2,5–59 . In five cases, the authors preferred a wait‐and‐see approach, 3,11,60,61 while in another seven cases, the authors reported a spontaneous regression of the pathology 42 . In five cases, in which the location was superficial, CO2‐laser therapy with the pinhole technique was preferred 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Vincenzo Abbate 1 | Giovanni Dell'Aversana Orabona 1 | Giovanni Audino 1 | Antonio Romano 1 | Paola Bonavolontà 1 | Daniela Russo 2 | Silvia Varricchio 2 | Roberto Ferrigno 1 | Giorgio Iaconetta 3 | Luigi Califano 1 and functional results. Herein, we introduce the technical description of a novel minimally invasive approach for nodular fasciitis removal, and present a literature review.…”
Section: A S E R E P O R T Nodular Fasciitis In Cervicofacial Region:...mentioning
confidence: 99%
See 2 more Smart Citations